ANALYSIS OF REPLACEMENT PART TIME INTERVAL DETERMINATION OF CRITICAL IN ENGINE WATER COOLANT PUMP TYPES KRI FPB57 - Sutrisno Sutrisno; Abdul Rahman; Bambang Suharjo; Rachmana F Antariksa (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Maintenance management is required and has a very vital role for a KRI types FPB57, considering the type KRI is one Alutsista Navy who have a high frequency activity, as well as the broad range of operations support capabilities are varied so that the automatic machine is also high activity and in the end reliability will decrease. Methodology Failure Mode Effects and Criticality Analysis (FMECA) is a widely recognized tool for the study and analysis of the reliability of the design or process. Many authors in the field have emphasized specifically the usefulness of this method and its limitations. At this writing considering the lifetime of the machine and the elements therein specifically the components of the water coolant pump has had a lifetime of more than 20 years, because it can be said that the components have entered a critical period. Based on the steps Failure Mode Effects and Criticality Analysis (FMECA) through the calculation of Risk Priority Number (RPN), so we can determine the critical components of acquired 9 of 19 chances damage that has critical component is Angular Bearings, Cylindrical Bearings, Spacer Ring, Water Seal, shaft Seal, Seal Slip Ring, Impeller, O'Ring and shaft. These components if damaged can lead to engine breakdown. From the optimization results indicate that the component replacement Cylindrical Bearings have the fastest time, ie 98 days. While the replacement of components with the longest time, which is a component Impeller 134 days. Besides obtain the most optimal replacement time of each component, also produced the cost of replacement is effective, it is proved by the value of the optimal CBR. CBR value for all types of components is less than 1 (CBR <1).Keywords : FMECA, Risk Priority Number, Reliability, Replacement Intervals,CBR.